Until the Dawn - Camden, Elizabeth; 1948- (Bethany House, a division of Baker Publishing Group, 2015)
"In 1898, an abandoned mansion overlooking the Hudson River Valley proves a refuge and resource for Sophie van Riijn in her volunteer work for the Weather Bureau until Quentin Vandermark, a long-lost heir of the estate, shows up"--
Keywords: Fiction; Man-woman relationships; Family secrets; Fiction; Hudson River Valley (N.Y. and N.J.); Fiction; Social life and customs; 19th century; Romance fiction; Historical fiction; Christian fiction